LMS-Based Assessment and Islamic Pedagogy: A Qualitative Case Study in an Indonesian Private University - Adiyono, Adiyono; Fitri, Agus Zaenul; Sanam, Anna Isabela (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This qualitative case study investigates the integration of LMS-based assessments in Islamic higher education, focusing on how prayerful pedagogical values come into alignment with the practices of digital evaluation. Conducted at a private Islamic university in the Republic of Indonesia, between February and June 2025, 16 students and two lecturer-participants in an Educational Evaluation course were involved in the research. Data collection was based on semi-structured interviews, focus group discussions, classroom observation, and an analysis of LMS documents. Data were analyzed with NVivo 14, according to the thematic concept of Braun and Clarke. The findings identified three key themes: pedagogical transparency, ethical awareness, and faith–technology alignment. Of note, in their discussions, participants felt that LMS assessment improved grading clarity, created opportunities for self-regulated learning, and helped enforce accountability, consistent with Islamic ethical principles such as amanah and adl. However, the major concerns raised with respect to digital examination servers were confidence in technology and equity of access. In conclusion, the study argues that when based on ethical and faith-based principles LMS assessment can promote transparency, academic honesty, and moral engagement in Islamic higher learning. Some implications are that institutional frameworks for integrating digital literacy, ethical orientation, and pedagogical innovation into the assessment practices are necessary.